Impact of Yeast Breeding for Elevated Glycerol Production on Fermentative Activity and Metabolite Formation in Chardonnay Wine - Prior, B.A.; Toh, T.H.; Jolly, N.; Baccari, C.; Mortimer, R.K. (South African Journal of Enology and Viticulture, 2017)
Glycerol in wine originates mainly as a by-product during fermentation by yeast and is thought to add to the body and smooth mouth-feel. We evaluated the properties of Chardonnay wine produced using various wine yeast strains of Saccharomyces cerevisiae and hybrid strains that were bred to produce elevated glycerol concentrations in laboratory trial experiments. The wine yeast strains (commercial strains or strains from culture collections) produced a mean glycerol and ethanol concentration of 4.38 and 101.2 g/L (12.8% v/v; n=26) respectively, whereas the glycerol and ethanol concentrations in wine made using the hybrid strains was 7.18 g/L and 96.0 g/L (12.2% v/v; n=15). Considerable variability in the glycerol-producing ability of the wine yeast and hybrid strains was apparent. Coupled to the higher glycerol levels formed by the hybrid strains, acetic acid, volatile acidity, acetoin, acetaldehyde and 2,3-butanediol levels were higher than the levels produced by the wine yeast strains. The levels of some of these metabolites were strongly linked to elevated glycerol production. The hybrid strains fermented the Chardonnay grape juice more slowly than the wine yeast strains, but in most instances dryness was achieved. The concentrations of miscellaneous metabolites (alcohols, acids and esters) were in most instances similar in the wine made with the wine yeast strains and hybrid strains, indicating that the breeding of yeast to produce higher glycerol levels has a minor influence on the production of these compounds. In a wine production experiment one hybrid yeast strain producing elevated glycerol levels yielded a Chardonnay wine with a better or equivalent body than wine made with commercial wine yeast strains, although the aroma and general quality were worse. These results suggest that further breeding and selection might yield yeast strains for fermentation that improves the body of wine without impacting on the overall balance of wine.